A camelid antibody candidate for development of a therapeutic agent against Hemiscorpius lepturus envenomation. Issue 9 (2nd June 2014) - Yardehnavi, Najmeh; Behdani, Mahdi; Bagheri, Kamran Pooshang; Mahmoodzadeh, Amir; Khanahmad, Hossein; Shahbazzadeh, Delavar; Habibi‐Anbouhi, Mahdi; Ghassabeh, Gholamreza Hassanzadeh; Muyldermans, Serge
Abstract : Hemiscorpius lepturus scorpionism poses one of the most dangerous health problems in many parts of the world. The common therapy consists of using antivenom antibody fragments derived from a polyclonal immune response raised in horses. However, this immunotherapy creates serious side effects, including anaphylactic shock sometimes even leading to death. Thus, many efforts have been made to introduce new replacement therapeutics that cause less adverse reactions. One of the most attractive approaches to replacing the available therapy is offered by single‐domain antibody fragments, or nanobodies (Nbs). We immunized dromedaries with H. lepturus toxin and identified a functional recombinant Nb (referred to as F7Nb) against heminecrolysin (HNc), the major known hemolytic and dermonecrotic fraction of H. lepturus venom. This Nb was retrieved from the immune library by phage display selection. The in vitro neutralization tests indicated that 17.5 nmol of the F7Nb can inhibit 45% of the hemolytic activity of 1 EC100 (7.5 μg/ml) of HNc. The in vivo neutralization tests demonstrated that F7Nb had good antihemolytic and antidermonecrotic effects against HNc in all tested mice. Surprisingly, F7Nb (8.75 nmol) neutralized 1 LD100 of HNc (10 μg) via an intracerebroventricular route or 1 LD100 (80 μg) via a subcutaneous route. All of the control mice died. Hence, this Nb is a potential leading novel candidate for treating H. lepturus scorpionism in the near future.—Yardehnavi, N., Behdani, M., Pooshang Bagheri, K., Mahmoodzadeh, A., Khanahmad, H., Shahbazzadeh, D., Habibi‐Anbouhi, M., Hassanzadeh Ghassabeh, G., Muyldermans, S. A camelid antibody candidate for development of a therapeutic agent against Hemiscorpius lepturus envenomation. FASEB J. 28, 4004‐4014 (2014). www.fasebj.org